Pressure-tuning of the photomagnetic response of heterostructured CoFe@CrCr-PBA core@shell nanoparticles. (17th February 2017) - Peprah, Marcus K.; VanGennep, Derrick; Quintero, Pedro A.; Risset, Oliva N.; Brinzari, Tatiana V.; Li, Carissa H.; Dumont, Matthieu F.; Xia, Jian-sheng; Hamlin, James J.; Talham, Daniel R.; Meisel, Mark W.
Graphical abstract: Externally applied pressure applied to CoFe@CrCr Prussian blue analogue core@shell nanoparticles shifts the magnetic ordering temperatures of the CoFe-PBA core, the CrCr-PBA shell, and the photo-CTIST of the CoFe-PBA core. Specifically, the magnetic ordering temperature of the CrCr-PBA shell shifted to higher temperatures, while the relaxation temperature of the photo-CTIST of the CoFe-PBA core moved to lower temperatures. Abstract: Using a home-made, anvil pressure-cell mounted to a probe suitable for use with a commercial magnetometer, the photo and thermal responses of the magnetism of CoFe@CrCr-PBA (PBA = Prussian blue analogue) core@shell nanoparticles were studied down to 5 K and up to 0.5 GPa in 100 G. The effect of pressure on the magnetic ordering temperatures of the CoFe-PBA core (≈25 K) and the CrCr-PBA shell (≈200 K) along with a shift of the relaxation temperature of the photo-CTIST (charge-transfer-induced spin-transition) of the CoFe-PBA core (≈125 K), were similar to the behaviors reported for the single-phase materials. Specifically, although the magnetic ordering temperature of the CrCr-PBA shell shifted to higher temperatures, the relaxation temperature of the photo-CTIST of the CoFe-PBA core moved to lower temperatures when the pressure was increased, thereby lowering the temperature range under which the CrCr-PBA component can be photoswitched.